2019
DOI: 10.1007/s42729-019-00119-7
|View full text |Cite
|
Sign up to set email alerts
|

Chestnut Response to Organo-mineral and Controlled-Release Fertilizers in Rainfed Growing Conditions

Abstract: In the context of climate change, chestnut fertilization is receiving great attention in the Mediterranean basin, due to the increase in the unpredictability of the pluviometric regime which makes it difficult to determine the optimal timing of fertilizer applications. The purpose of this work was to assess the suitability of fertilizers with mechanisms for nutrient protection on the increase of tree nutritional status and crop productivity. Four fertilizers with restricted nutrient solubility were tested:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
13
1
Order By: Relevance
“…In this study, leaf B levels often appeared below the lower limit of the sufficiency range (Arrobas et al 2018). Previous studies in the region also reported B as one of the elements which can cause nutritional disorders in chestnut trees (Portela et al 2011(Portela et al , 2015Rodrigues et al 2019).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In this study, leaf B levels often appeared below the lower limit of the sufficiency range (Arrobas et al 2018). Previous studies in the region also reported B as one of the elements which can cause nutritional disorders in chestnut trees (Portela et al 2011(Portela et al , 2015Rodrigues et al 2019).…”
Section: Discussionsupporting
confidence: 51%
“…It should also be noted that leaf Ca levels were low if compared with the sufficiency range, and the trees of Salgueiros, grown on a more acidic soil and with less Ca in the exchangeable complex (Table 2), revealed levels of Ca below the lower limit of the sufficiency range. In previous studies, it has already been recorded that Ca may appear below the sufficiency range in some chestnut orchards of the region grown in acidic soils (Arrobas et al 2018;Rodrigues et al 2019). In Salgueiros, the applied lime did not raise leaf Ca levels to the sufficiency range, probably because the effectiveness of liming might have been reduced, due to not being incorporated into the soil.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This seems to be a contradictory result since K is usually associated with increasing plant growth (Hawkesford et al 2012). However, K tends to vary greatly between cropping conditions and years (Rodrigues et al 2020). Otherwise, probably this is due to the variability in soil reduction conditions along the fields and the subsequent nutrient interaction that takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Osmocote® is a polymer-coated fertilizer that performs well in seedling production in containers (Machado et al 2011;Mendonça et al 2004;Pereira et al 2000). Despite their easy application and contribution to nutrient loss reduction, economical aspects should be taken into account, since slow release fertilizers are far more costly than their conventional counterparts (Rodrigues et al 2019).…”
Section: Introductionmentioning
confidence: 99%